Isolated Foveal Photoreceptor Disruption: Two Case Reports with Clinical Features and Imaging Findings - Gülce Begüm Kotanoğlu; Pınar Çiçek Kaya; Berrak Şekeryapan Gediz (Academic Journal of Health, 2026)
Isolated foveal photoreceptor disruption (IFPD) is an uncommon, typically self-limiting optical coherence tomography (OCT) finding seen in various retinal disorders. This report represents two cases of unilateral IFPD presenting with decreased visual acuity. The first patient, a 40-year-old woman, presented with an idiopathic defect that showed partial spontaneous recovery. The second patient, a 33-year-old man, presented with permanent damage and a central scotoma following direct solar exposure. OCT revealed localized defects confined to the ellipsoid and interdigitation zones in both patients. These cases emphasize the critical role of OCT in distinguishing IFPD from other macular pathologies and the need for longitudinal follow-up. Key Words: Isolated foveal photoreceptor disruption; macular hole; macular microhole; optical coherence tomography